Good Governance in the Bioeconomy. (13th January 2017) - Devaney, Laura; Henchion, Maeve; Regan, Áine
Summary: In response to growing societal and environmental challenges, the concept of the bioeconomy has emerged in Europe, shifting society away from fossil fuels to utilising renewable biological resources to meet food, feed, fuel and material needs. The bioeconomy poses unique questions for governing stakeholders, with a need to simultaneously consider issues of food, fuel and resource security, competition for biomass supply, environmental degradation, climate change, economic growth and rural development. It thus represents one of the most politically complex areas facing agri‐food and rural resource sectors internationally. Further development of the bioeconomy and its impact on society will depend on how it is governed. It is widely accepted that good governance will require input from a diverse range of stakeholders beyond traditional government intervention. In this article, we explore the application of good governance principles as a common set of objectives for European stakeholders to strive towards, with particular consideration given to the principles of accountability and participation. How these elements need to be addressed as a priority for the economic, environmental and social sustainability of the future European bioeconomy is highlighted. Abstract : In response to growing societal and environmental challenges, the concept of the bioeconomy has emerged in Europe, shifting society away from fossil fuels to utilising renewable biological resources to meet food, feed, fuel and material needs. The bioeconomy poses unique questions for governing stakeholders, with a need to simultaneously consider issues of food, fuel and resource security, competition for biomass supply, environmental degradation, climate change, economic growth and rural development. It thus represents one of the most politically complex areas facing agri‐food and rural resource sectors internationally. Further development of the bioeconomy and its impact on society will depend on how it is governed. Abstract : Le concept de bioéconomie a émergé en Europe en réponse aux défis grandissants au plan sociétal et environnemental. Il réoriente la société fondée sur les combustibles fossiles vers l'utilisation de ressources biologiques renouvelables pour remplir les besoins en aliments, aliments du bétail, combustibles et matériaux. La bioéconomie pose des questions uniques aux parties prenantes en termes de gouvernance, car plusieurs questions doivent être considérées simultanément: la sécurité en termes d'alimentation, de combustibles et de ressources, la concurrence pour l'offre de biomasse, la dégradation de l'environnement, le changement climatique, la croissance économique et le développement rural. Elle représente donc l'un des domaines les plus complexes pour l'action publique auxquels sont confrontés les secteurs de l'agroalimentaire et des ressources rurales au plan international. Le développement plus avant de la bioéconomie et de son incidence sur la société dépendra de la façon dont il est géré. Il est largement acquis qu'une bonne gouvernance demandera la contribution d'une variété de parties prenantes au‐delà des interventions traditionnelles des pouvoirs publics. Dans cet article, nous explorons l'application des principes de bonne gouvernance à un ensemble commun d'objectifs pour que les parties prenantes européennes aillent de l'avant. Nous examinons plus particulièrement les principes de responsabilité et de participation, et nous mettons en évidence la façon dont ces éléments doivent être abordés comme une priorité pour la durabilité économique, environnementale et sociale d'une future bioéconomie européenne. Abstract : Als Reaktion auf die wachsenden gesellschaftlichen und ökologischen Herausforderungen entstand in Europa das Konzept der Bioökonomie. Es beschreibt den Wandel hin zu einer Gesellschaft, die anstelle fossiler Brennstoffe erneuerbare biologische Ressourcen nutzt, um ihren Bedarf an Lebens‐ und Futtermitteln sowie an Brennstoffen und Rohwaren zu decken. Die Bioökonomie stellt führende Akteure vor ganz besondere Aufgaben, denn sie müssen sich zeitgleich mit Fragen zu Ernährung, Energie, Rohstoffsicherheit, Wettbewerb um die Versorgung mit Biomasse, Verschlechterung der Umweltbedingungen, Klimawandel, Wirtschaftswachstum und ländlicher Entwicklung auseinandersetzen. Die Bioökonomie ist daher im Hinblick auf die internationalen Agrar‐ und Ernährungssektoren sowie die ländlichen Ressourcen einer der komplexesten Politikbereiche. Die weitere Entwicklung der Bioökonomie und ihre Auswirkungen auf die Gesellschaft werden davon abhängig sein, wie sie rechtlich geregelt sein wird. Es besteht weitgehend Übereinstimmung darin, dass Good Governance den Input vieler unterschiedlicher Akteure über die klassische staatliche Intervention hinaus erfordert. In diesem Beitrag untersuchen wir die Anwendung von Good Governance‐Prinzipien im Sinne eines gemeinsamen, erstrebenswerten Bündels an Zielen für europäische Akteure, wobei besonders die Prinzipien der Rechenschaftspflicht und der Teilhabe berücksichtigt werden. Wie diese Elemente insbesondere für die wirtschaftliche, ökologische und soziale Nachhaltigkeit der zukünftigen europäischen Bioökonomie eingesetzt werden sollten, wird in diesem Beitrag beleuchtet.